SIYASAH DUSTURIYAH PERSPECTIVE ON LAW NUMBER 6 OF 2023 CONCERNING JOB CREATION AFTER THE CONSTITUTIONAL COURT DECISION NUMBER 91/PUU-XVIII/2020 - Aldani, Risma; Nurhikma, Nurhikma; Putri, Siska Elasta (Institut Agama Islam Negeri Batusangkar, 2024)
This study is set to discover the establishment of Law Number 6 of 2023 on Job Creation (Law 6/2023) as a response to the Constitutional Court Decision Number 91/PUU-XVIII/2020. This study uses normative juridical method. Based on the study, it was found that Law 6/2023 aims to fulfill people's right to decent employment as stipulated in Article 27 of the 1945 Constitution. The formulation process began with the Job Creation Law using the omnibus law technique, followed by a formal test by the Constitutional Court which resulted in Decision Number 91/PUU-XVIII/2020.